2011
DOI: 10.1016/j.neurobiolaging.2009.05.012
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid impairs axonal BDNF retrograde trafficking

Abstract: The neurotrophin, brain-derived neurotrophic factor (BDNF), is essential for synaptic function, plasticity and neuronal survival. At the axon terminal, when BDNF binds to its receptor, tropomyosin-related kinase B (TrkB), the signal is propagated along the axon to the cell body, via retrograde transport, regulating gene expression and neuronal function. Alzheimer disease (AD) is characterized by early impairments in synaptic function that may result in part from neurotrophin signaling deficits. Growing evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
125
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(135 citation statements)
references
References 110 publications
8
125
2
Order By: Relevance
“…Consistent with the hypothesis that A␤-mediated synaptic dysfunction involves disrupted BDNF signaling, we have found that soluble A␤ impairs retrograde axonal trafficking of the BDNF receptor, TrkB (22). Retrograde axonal transport of the BDNF-TrkB complex to the soma drives downstream signaling events important for neuronal health, survival, and plasticity, including CREB-dependent gene transcription (24).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with the hypothesis that A␤-mediated synaptic dysfunction involves disrupted BDNF signaling, we have found that soluble A␤ impairs retrograde axonal trafficking of the BDNF receptor, TrkB (22). Retrograde axonal transport of the BDNF-TrkB complex to the soma drives downstream signaling events important for neuronal health, survival, and plasticity, including CREB-dependent gene transcription (24).…”
supporting
confidence: 84%
“…Mature BDNF-GFP was further purified by size exclusion chromatography (Amicon YM-50) where the flow-through contained the protein of interest. BDNF-GFP is indistinguishable from BDNF both biochemically and biologically (38,39), and we previously confirmed that our purified BDNF-GFP was biologically active (22). The BDNF-GFP concentration was determined by BDNF ELISA (Promega).…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…20 The CNA circuits can be used to establish many other heterotypic co-cultures to model different neurobiological interactions, such as the neuromuscular junction, the role of glial cells during axon myelination, [46][47][48] immune cell scenarios implicated in autoimmunity-based neurodegeneration and spatially defined cues for neuronal stem cell differentiation. In addition, the compartmentalized nature of the co-culture systems enable investigations into the propagation of materials and pathological responses with notable examples being amyloid trafficking, 49 toxin dissemination, especially nanoparticulates such as manganese, and the distribution of virus and prion infectious agents. The compartmentalised systems also provide a spatially standardized imaging display for network integrity measurements and functional assays employing fluorescent Ca 2+ reporters.…”
Section: Outlook and Applicationsmentioning
confidence: 99%
“…Alternatively, a disruption of BDNF signaling would likely reduce or prevent XBP1-dependent amelioration of AD-like pathology (19). In vivo and in vitro studies have demonstrated that oligomeric Aβ alters BDNF expression/function by downregulating its transcripts or impairing axonal transport, with subsequent adverse effects (159)(160)(161)(162)(163)(164)(165). Oligomeric Aβ also reduces BDNF secretion by dendritic cells in humans, thereby decreasing neurotrophic supports for neurons and causing brain damage (166).…”
Section: Potential Mediators Of Xbp1 Signaling In Neuronsmentioning
confidence: 99%